2015
DOI: 10.1016/j.vaccine.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential immune responses to HIV-1 envelope protein induced by liposomal adjuvant formulations containing monophosphoryl lipid A with or without QS21

Abstract: Liposomes have shown promise as constituents of adjuvant formulations in vaccines to parasitic and viral diseases. A particular type of liposomal construct, referred to as Army Liposome Formulation (ALF), containing neutral and anionic saturated phospholipids, cholesterol, and monophosphoryl lipid A (MPLA), has been used as an adjuvant for many years. Here we investigated the effects of physical and chemical changes of ALF liposomes on adjuvanted immune responses to CN54 gp140, a recombinant HIV-1 envelope pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 47 publications
0
65
1
Order By: Relevance
“…These adjuvants often incorporate components that stimulate innate immune system receptors like Toll-like receptors (TLRs) and the inflammasome. The Walter Reed Army Institute of Research Laboratory of Adjuvant and Antigen Research has developed an Army Liposome Formulation (ALF) family of adjuvants that increase immunogenicity of a number of different vaccine platforms against a variety of pathogens, including HIV, Plasmodium falciparum, and Neisseria meningitidis (20)(21)(22)(23)(24). ALF is a liposome-based formulation containing a potent activator of TLR4, a synthetic form of monophospholipid A (MPLA) known as 3D-PHAD (Avanti Polar Lipids).…”
mentioning
confidence: 99%
“…These adjuvants often incorporate components that stimulate innate immune system receptors like Toll-like receptors (TLRs) and the inflammasome. The Walter Reed Army Institute of Research Laboratory of Adjuvant and Antigen Research has developed an Army Liposome Formulation (ALF) family of adjuvants that increase immunogenicity of a number of different vaccine platforms against a variety of pathogens, including HIV, Plasmodium falciparum, and Neisseria meningitidis (20)(21)(22)(23)(24). ALF is a liposome-based formulation containing a potent activator of TLR4, a synthetic form of monophospholipid A (MPLA) known as 3D-PHAD (Avanti Polar Lipids).…”
mentioning
confidence: 99%
“…Previous results obtained by our group demonstrated that DPPC: Cho (1:1) Lp encapsulating human epidermal growth factor are able to modulate the anti–human epidermal growth factor Ab response in mice to a mixed Th1/Th2 response, but they favored a Th1 pattern (50). The ability of Lp/OVA/StII to induce a Th1/Th2 mixed pattern could be desirable for a candidate vaccine that is addressed not only to intracellular targets (51). …”
Section: Resultsmentioning
confidence: 99%
“…The synthetic GIL (GILGFVFTL) peptide corresponds to the influenza A virus matrix protein, Mp58–66 and was obtained from Mimotopes Inc. The GIL peptide was encapsulated in liposomes containing neutral and anionic saturated phospholipids, cholesterol, and monophosphoryl lipid A (MPLA) as described 33 . The liposomes were obtained from the Laboratory of Adjuvant and Antigen Research, US Military HIV Research Program, Walter Reed Army Institute of Research.…”
Section: Methodsmentioning
confidence: 99%